Gender Inequality in School Education with Special Reference to North East India - Nongkynrih, Deigracia (INDIAN EDUCATIONAL REVIEW, 2013)
Education is viewed as a key factor in the development of human capital. However, in India it is marked by high levels of gender inequality. The objective of this paper is to examine the extent of gender inequality in school education (up to higher secondary) for the North East (NE) states vis-à-vis the all India level. Secondary data from various sources has been employed to examine this issue. The study concludes that gender disparity is very much in existence in NE states though it is relatively less than the all India level. Further the gender disparity is revealing declining trends in past decade in these states but at a slower pace. The smaller states of Mizoram and Meghalaya are showing better gender equality than the relatively larger states of Assam and Arunachal Pradesh in NE.